Addressing Wicked Problems Through Empathy-enhanced Design-based Team Learning: Illustrating Implicit and Explicit Approach - Van Maele, Jan; Bairaktarova, Diana; Bloemen, Veerle; Direito, Inês (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This practice paper aims at contributing to the conversation about caring pedagogies and sustainable engineering education by focusing on empathy, ‘the ability to understand people by perceiving or experiencing their life situations’. Based on our experiences as engineering educators in Europe and North America, we offer examples of how design-based learning can be enhanced through the purposeful integration of empathy nurturing activities at every stage of the team project work. More specifically, we describe an approach in which empathy is an explicit focus of learning activities and an approach in which empathy is a more implicit learning outcome that is embedded within broader transversal learning goals. The design projects we offer as illustrations center on ‘wicked problems’ that affect various stakeholders beyond technical experts. By encouraging a decentralized, multi-perspective approach, wicked problems can enhance a caring pedagogy in project-based learning. By integrating empathy with technical expertise, be it explicitly or in more implicit ways, we highlight the crucial role of emotional intelligence, ethical decision- making, and interpersonal skills in engineering practice—an approach that cultivates responsibility and equips individuals to tackle real-world challenges with compassion and ethical insight.